2018
DOI: 10.1002/sea2.12122
|View full text |Cite
|
Sign up to set email alerts
|

Gendered redistribution and family debt: The ambiguities of a cash transfer program in Brazil

Abstract: Latin American conditional cash transfer (CCT) programs are usually regarded as policies of social protection that question the neoliberal agenda. This article suggests instead that the Brazilian CCT Bolsa Família (Family Grant) is ambiguous in the sense that it was consolidated in association with policies of expansion of financial markets in the country under the rubric of social rights and female emancipation. To analyze the ambiguities of the program, we first delve into official federal documents and prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The benefits of this increased social capital were lower default risk, strengthened social networks, and greater information sharing. In contrast, however, Badue and Ribeiro (2018) found that borrowers in Brazil preferred owing to a bank rather than to a friend because “the friend is always around.”…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The benefits of this increased social capital were lower default risk, strengthened social networks, and greater information sharing. In contrast, however, Badue and Ribeiro (2018) found that borrowers in Brazil preferred owing to a bank rather than to a friend because “the friend is always around.”…”
Section: Resultsmentioning
confidence: 95%
“…Its major critique, however, is that it entrenches unequal, hierarchical global and local relationships. Through the financialization of the poor, it promulgates a cycle of indebtedness and dependency (Badue and Ribeiro 2018).…”
Section: Microlending—a Brief Introductionmentioning
confidence: 99%
“…Another, as the OPE perspective identifies, is that national and international political institutions generate them. Both sources are well illustrated in Badue and Ribeiro's (2018) research. They demonstrate that a cash transfer program promoted by the Brazilian state and called Bolsa Familia is appropriated and manipulated by the beneficiaries for different relational goals.…”
Section: Financialization As the Expanded Use Of Financial Relationalmentioning
confidence: 87%
“…La desregulación del mercado del crédito en las sociedades modernas puede motivar la aprobación de créditos a usuarios financieros que verdaderamente no tienen posibilidades de pagar (Kus, 2015). Este aspecto resulta especialmente relevante porque, cuando las familias se encuentran en situación de vulnerabilidad, se pueden generar esquemas inestables de financiación del gasto que solo conducen a los deudores a situaciones peores (Badue & Ribeiro, 2018).…”
Section: Introductionunclassified